IMPLEMENTASI PENDIDIKAN PROFETIK DALAM MEMBENTUK KARAKTER SISWA DI MADRASAH ALIYAH MAMBAUL ULUM BATA-BATA PANAAN PALENGAAN PAMEKASAN - Supri yadi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
This research was from the problem of student morality which was increasingly worrying, not only because of the sophistication of technology and information, but because the basic character was very fragile. Education for him did not have an impact on building a strong character. The purpose of this research, to identify and describe: First, Student Character, Second, Implementation of Prophetic Education in shaping student character, and Third, supporting and inhibiting factors of Implementation of Prophetic Education in shaping student character in Madrasah Aliyah Mambaul Ulum Bata- Bata Panaan Palengaan Pamekasan. This research used a type of qualitative research. Data and documents were collected and compiled using in-depth interview techniques, participant observation and documentation studies. The data and documents were then checked for validity through triangulation of methods and sources. Furthermore, the data and documents were analysed descriptively qualitatively. Based on the results of the study, the character of students in MA. Mambaul Ulum Bata-Bata actually had existed since time immemorial. However, the existing characters were getting better and better through the madrasa environment which is designed with prophetic traditions. The implementation of prophetic education in shaping the character of students, appeared in the existing system, in three forms or ways, among others; First, through learning; Second, through madrasa management; and Third, through studentship. The supporting factors of the implementation of prophetic education in shaping the character of students were support from boarding school caregivers, educators who were alumni of the boarding school and the facilities were quite complete. While the obstacle was the absence of worship infrastructure that can accommodate all students. Penelitian ini berangkat dari persoalan tentang moralitas siswa yang semakin menghawatirkan, tidak saja karena kecanggihan teknologi dan informasi, namun karena dasar karakternya yang sangat rapuh, Pendidikan baginya tidak memberikan dampak pada bangunan karakter yang kuat. Tujuan penelitian ini, untuk mengetahui dan mendeskripsikan : Pertama, Karakter Siswa, Kedua, Implementasi Pendidikan Profetik dalam membentuk karakter siswa, dan Ketiga, faktor pendukung dan penghambat Implementasi Pendidikan Profetik dalam membentuk karakter siswa di MA. Mambaul Ulum Bata-Bata Panaan Palengaan Pamekasan. Penelitian ini menggunakan jenis penelitian kualitatif. Data dan dokumen dikumpulkan dan dihimpun dengan menggunakan teknik wawancara mendalam, observasi partisipan dan studi dokumentasi. Data dan dokemen tersebut kemudian diperiksa validitasnya melalui triangulasi metode dan sumber. Selanjutnya data dan dokumen tersebut dianalisis secara deskriptif kualitatif. Berdasarkan hasil penelitian, karakter siswa di MA. Mambaul Ulum Bata-Bata sejatinya sudah ada sejak sedia kala. Namun demikian, karakter yang ada semakin meningkat dan baik melalui lingkungan madrasah yang didesain dengan tradisi profetik. Implementasi pendidikan profetik dalam membentuk karakter siswa, nampak pada sistem yang ada, dengan tiga bentuk atau cara antara lain; Pertama, melalui pembelajaran; Kedua, melalui manajemen madrasah; dan Ketiga, melalui kesiswaan. Adapun faktor pendukung dari pelaksanaan pendidikan profetik dalam membentuk karakter siswa, ialah dukungan dari pengasuh pondok pesantren, pendidik yang syarat alumni pondok dan sarana yang cukup lengkap. Sedangkan penghambatnya adalah tidak adanya prasarana ibadah yang dapat menampung semua siswa.